To what extent can the biogeochemical cycling of mercury modulate the measurement of dissolved mercury in surface freshwaters by passive sampling?. (June 2020) - Bretier, M.; Dabrin, A.; Billon, G.; Mathon, B.; Miège, C.; Coquery, M.
Abstract: Mercury (Hg) is a pollutant of global concern owing to its great toxicity even at very low concentrations. Its toxicity depends on its chemical forms evidencing the importance to study its speciation. Dissolved Hg (Hg(d) ) and methylmercury (MeHg(d) ) monitoring in surface freshwaters represents a great challenge because of their very low concentrations and substantial temporal variability at different timescales. The Hg(d) temporal variability depends on the environmental conditions such as the hydrology, water temperature, redox potential (Eh), and solar photo cycle. Passive samplers represent an alternative to improve the assessment of Hg(d) and MeHg(d) concentrations in surface freshwaters by integrating their temporal variability. An original sampling strategy was designed to assess the relevance of 3-mercaptopropyl DGT (Diffusive Gradient in Thin films) to integrate in situ the temporal variations of labile Hg (Hg(DGT) ) and MeHg (MeHg(DGT) ) concentrations. This strategy was implemented on two rivers to study the dynamics of Hg(d), Hg(DGT), MeHg(d) and MeHg(DGT) at diurnal and annual timescales. We evidenced that Hg(DGT) and MeHg(DGT) concentrations were generally consistent with discrete sampling measurements of Hg(d) and MeHg(d) in dynamic surface freshwaters. However, Hg(DGT) concentrations were overestimated (2–16 times higher) in case of low flow or low water depth, low suspended particulate matter (SPM) concentrations and elevated daily photoperiod. The most probable hypothesis is that such conditions promoted Hg 0 production, and resulted in Hg 0 uptake by DGT. Thus, attention should be paid when interpreting Hg(DGT) concentrations in surface freshwaters in environmental conditions that could promote Hg 0 production. Highlights: DGT is relevant to integrate annual/diurnal variations of labile Hg concentrations. Labile Hg concentration might be overestimated by DGT passive sampling in freshwaters. The overestimation was attributed to Hg 0 capture occurring under favorable conditions. ID-GC-ICP-MS enables to quantify representative average MeHg concentration in DGT.